Trophic state index validation based on the phytoplankton functional group approach in Amazon floodplain lakes. Issue 3 (3rd July 2019) - Bomfim, Eudes de Oliveira; Kraus, Cleber Nunes; Lobo, Maria Tereza M. P. S.; Nogueira, Ina de Souza; Peres, Lucas Garcia Magalhães; Boaventura, Geraldo Resende; Laques, Anne-Elisabeth; Garnier, Jérémie; Seyler, Patrick; Marques, David Motta; Bonnet, Marie-Paule
ABSTRACT: Many trophic indices have been constructed for temperate aquatic environments, but few have proved reliable for tropical environments. Indices constructed on the basis of nutrients may not be effective for describing the trophic state because the fractions of nitrogen and phosphorus differ in their potential to predict the nutrient limitation in tropical aquatic environments. We developed an index based on the phytoplankton Reynolds functional groups for an Amazonian floodplain lake from samples collected during 2 contrasting hydrological periods (rising and flushing) and compared it with the index initially proposed by Carlson in 1977 and further adapted to tropical environments by Toledo in 1990. The functional group and Carlson indices matched only 37% and 56% of the sample units collected during the rising and flushing periods, respectively. Our study confirms the difficulty of assessing trophic states using only phosphorus and chlorophyll a in tropical floodplain lakes. In this environment (1) nitrogen may significantly limit phytoplankton growth and (2) complex phytoplankton–nutrient relationships occur during the hydrological cycle that cannot be accounted for through a simple phosphorus and chlorophyll a formula.